The troll children's christmas wish - Cantillon, Eli Aleksanersen (Montreal, Canada : Tormont, 1992)
Troll Mother said Christmas was only for people children, but the troll children didn't want to believe her. After all, isn't Christmas for everybody? So Aja and her little troll brothers set out in search of Father Christmas.
Keywords: Trolls -- Fiction; Christmas stories -- Fiction